User-centered design of online learning communities - Lambropoulos, Niki; Zaphiris, Panayiotis (My University, 2007)
User-centered design (UCD) is gaining popularity in both the educational and business sectors. This is due to the fact that UCD sheds light on the entire process of analyzing, planning, designing, developing, using, evaluating, and maintaining computer-based learning. User-Centered Design of Online Learning Communities explains how computers can be used to augment human intellect for productivity and innovation, both nationally and globally. This book gives guidance to all stakeholders involved in online learning: organizations and businesses, developers, tutors, students, and evaluators; as well as provides best practices for the different phases of developing online learning communities from the analysis and design phase to the development, use, evaluation, and maintenance stage.